Hybridising Accounting and Caring: A Symmetrical Study of how Costs and Needs are Connected in Danish Child Protection Work - Ida Schrøder (Copenhagen Business School (CBS), 2018)
With this dissertation, I aim to find out how it is possible for statutory child protection workers to reach decisions when elements as different as a child's needs and the costs of a service are to be connected in the process. How is it possible, for instance, to count costs and sense the needs of a child at the same time? The purpose of inquiring into this question is to investigate the practices involved in `hybridising' accounting and caring practices. As a concept, `hybridity' denotes the process of bringing together elements that are normally found separately – hybridisation – and the outcome – a hybrid – of this process. This concept suggests that accounting co-exists with the practices it is a part of. The question of how hybridisation between accounting and caring practices takes place has been investigated in the research field of public sector accounting research (PSAR). Two main arguments have developed within this field of research: 1) In one strain of research, inspired by the work of Foucault, it is generally argued that hybridisation happens behind the backs of the caring professions, and causes them to pay less attention to the social needs of clients. Accordingly, researchers should pay attention to how tools and techniques transform working practices. 2) In another strain of research, inspired by New Institutional Theory, it is argued that hybridisation is a process that happens inside the minds of persons, as the logics of how to make decisions compete and multiply. Accordingly, researchers should pay attention to how constellations of logics vary. Despite their emphasis on “the practices” of the caring professions, these strains of research are unclear about how, when and where hybridisation happens in the day-to-day practices of social- and health care work. We do not know, for instance, whether costs are taken into account before, during, or after a doctor, for example, decides how to operate – or throughout the entire process. And we do not know how calculations of the costs of medical- and social services are practically involved in decisions about how to allocate resources to individuals.
hdl:10398/9688
Keywords: 650